Effectiveness of Behavioral Counseling with Participant Modeling Techniques on Students' Communication Ethics when Playing Mobile Legends Games - Rahmi, Siti; Nurwahidah; Anwar (Department of Guidance and Counseling, FIP, Undiksha, 2025)
The popularity of mobile online games among students has led to various social impacts, one of which is the decline in communication ethics during gameplay. Many students engage in inappropriate, aggressive, and impolite verbal interactions while playing, indicating weak digital ethical awareness among adolescents. This study aims to examine the effectiveness of behavioral counseling using participant modeling techniques to improve students’ communication ethics during online gaming activities. A quantitative approach with a One Group Pretest-Posttest Design experimental method was employed in this research. The study involved a population of 357 students, from which 10 students were purposively selected as research subjects based on their tendency to engage in unethical communication during gaming. Data were collected using a communication ethics scale questionnaire, and analyzed through a paired sample t-test. The findings revealed a significant difference between pretest and posttest scores, with a sig. (2-tailed) value of 0.000 < 0.05 and a t-value of 6.239 > 2.228. It can be concluded that the participant modeling technique is effective in fostering students’ ethical behavior in digital interactions during mobile gaming. This study implies that school counseling services should adopt this approach as an intervention model to cultivate students’ digital ethics.